Childhood Vasculitis Syndrome Mimicking Guillain Barre Syndrome - Pradeep Kumar Jena; Swasthi Kabi Satpathy; Sarthak Naik; Alok Satyaprakash Nayak (Wolters Kluwer Medknow Publications, 2022)
Background: Childhood vasculitis is a heterogeneous disorder, characterized by inflammation of the blood vessel walls. Multiple organs and/or tissues are affected, either simultaneously or successively. Vascular neuropathy occurs when the vasa nervorum is affected. Presentation includes mononeuritis multiplex, acute motor/motor-sensory axonal neuropathy, pure sensory neuropathy, and chronic inflammatory demyelinating polyneuropathy. Making a diagnosis is a challenge when neurological manifestations appear for the first time or are isolated. Clinical Description: A 12-year-old girl presented with acute pain and progressive weakness of both lower limbs for 12 days, followed by diffuse abdominal pain and low-grade fever. Salient neurological findings were diminished power and hyporeflexia in all limbs. Guillain-Barre syndrome was suspected in view of symmetric ascending paralysis and a suggestive nerve conduction study. The child had neutrophilic leukocytosis but sterile cultures. The successive development of inflammatory demyelinating polyneuropathy, persistent fever, vasculitic phenomena (hypertension, severe myalgia, rashes, multiple infarcts, acute renal cortical necrosis, and gangrene of the digit), and elevated acute-phase reactants was suggestive of a multisystemic small-vessel and medium-sized vasculitis syndrome, such as polyarteritis nodosa (PAN). A diagnosis of PAN was established based on the satisfaction of clinical criteria. Management: The patient was administered pulse methylprednisolone and oral steroids, with which there was a dramatic recovery. Monthly cyclophosphamide was continued in view of major systemic involvement. Conclusion: Early recognition and management of childhood vasculitis syndrome is associated with good outcomes.